Phylogenomic analysis of Anabaenopsis elenkinii (Nostocales, Cyanobacteria) - Delbaje, Endrews; Andreote, Ana Paula D.; Pellegrinetti, Thierry A.; Cruz, Renata B.; Branco, Luis H. Z. [UNESP]; Fiore, Marli F. (Microbiology Soc, 2021)
The saline- alkaline lakes (soda lakes) are the habitat of the haloalkaliphilic cyanobacterium Anabaenopsis elenkinii, the type species of this genus. To obtain robust phylogeny of this type species, we have generated whole- genome sequencing of the bloom-forming Anabaenopsis elenkinii strain CCIBt3563 isolated from a Brazilian soda lake. This strain presents the typical morphology of A. elenkinii with short and curved trichomes with apical heterocytes established after separation of paired intercalary heterocytes and also regarding to cell dimensions. Its genome size is 4 495 068 bp, with a G+C content of 41.98 %, a total of 3932 potential protein coding genes and four 16S rRNA genes. Phylogenomic tree inferred by RAxML based on the alignment of 120 conserved proteins using GTDB- Tk grouped A. elenkinii CCIBt3563 together with other genera of the family Aphanizomenonaceae. However, the only previous available genome of Anabaenopsis circularis NIES-21 was distantly positioned within a clade of Desikacharya strains, a genus from the family Nostocaceae. Furthermore, average nucleotide identity values from 86?98 % were obtained among NIES-21 and Desikacharya genomes, while this value was 76.04 % between NIES-21 and the CCIBt3563 genome. These findings were also corroborated by the phylogenetic tree of 16S rRNA gene sequences, which also showed a strongly supported subcluster of A. elenkinii strains from Brazilian, Mexican and Kenyan soda lakes. This study presents the phylogenomics and genome- scale analyses of an Anabaenopsis elenkinii strain, improving molecular basis for demarcation of this species and framework for the classification of cyanobacteria based on the polyphasic approach.
Keywords: Cyanobacteria; Genome; Soda lake; Ecology